Gender and leadership development in undergraduate computing: a closer look at women's leadership conceptions. Issue 4 (1st October 2020) - Blaney, Jennifer M.
ABSTRACT: Background and Context: Women remain underrepresented in undergraduate computing, student leadership roles, and computing leadership positions after college. This study provides insight into these inequities by examining gender and leadership conceptions among computing undergraduate students. Objective: Guided by leadership identity development and undergraduate socialization theories, I examine the relationship between college experiences and computing students' leadership confidence, focusing on the moderating role of gender. Method: This study uses regression analysis, relying on a longitudinal sample of 1, 081 computing students. Findings: Findings highlight the role of family, peer, and faculty interactions in predicting leadership outcomes, with special attention to conditional effects by gender. Additionally, findings reveal that leadership confidence in computing appears to be more malleable than students' general confidence in their leadership abilities. Unfortunately, I found that computing leadership confidence actually declines over time and that computing and general leadership ratings misaligned, such that women reported lower computing leadership confidence, relative to their general leadership confidence. Implications: Findings point to the importance of discipline-specific inquiry on college student leadership development. Other findings underscore the importance of fostering high quality student-faculty interactions in computing.